Youth at risk by the use of internet - Lugani, Carlos Fabián (2014)
Everyday we are surprised by new stories of kids and teenagers who have been harassed on the Internet. The wide scope of Internet with its social network and new technologies and applications, allows spreading anonymous information like photos, videos or comments almost instantly. The results could vary from bullying to cheating or discrimination of any kind. The use of technology is in our daily life and even kids at an early age have access to it. The tools available to fight this problem are not enough. The government, families and school teachers are not prepared to deal with this kind of risks. Considering this reality, the possible solutions will be analyzed in order to educate kids and teenagers to be aware of the risks so they could learn the tools to deal with undesired situations.